2009
DOI: 10.1089/lap.2008.0088
|View full text |Cite
|
Sign up to set email alerts
|

The Peritoneal Fibrinolytic Response to Conventional and Laparoscopic Colonic Surgery

Abstract: Both conventional and laparoscopic surgery inflict a decrease in tPA antigen and its specific activity. Peritoneal hypofibrinolysis initiates more rapidly during conventional, compared to laparoscopic, surgery, but at the conclusion of the surgery, the effect was the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Intraabdominal damage due to reductions in peritoneal fibrinolytic activity are among the main triggers of adhesion formation [6,17]. As a consequence of peritoneal lesions the production of tPA, the main fibrinolytic stimulator, decreases rapidly and the release of PAI-1 is simultaneously stimulated [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Intraabdominal damage due to reductions in peritoneal fibrinolytic activity are among the main triggers of adhesion formation [6,17]. As a consequence of peritoneal lesions the production of tPA, the main fibrinolytic stimulator, decreases rapidly and the release of PAI-1 is simultaneously stimulated [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of foreign body material, such as sutures or mesh implants, and/or infection will exacerbate this imbalance in fibrinolysis resulting in excessive fibrin deposition and an increased risk of adhesion development. Many studies have demonstrated that reducing tissue plasminogen activator (tPA) or increasing PAI-1 results in increased adhesion formation whereas increasing tPA and decreasing PAI-1 activity induces less adhesions to form [ 73 , 74 , 75 , 76 ]. Of relevance, Hellebrekers and colleagues found that in patients undergoing pelvic surgery, preoperative high PAI-1 and low tPA levels were positively correlated with extent of postoperative adhesion development [ 77 ].…”
Section: Serosal Repair and Adhesion Formationmentioning
confidence: 99%
“…Η χειρουργική προσέγγιση -ανοιχτή έναντι της λαπαροσκοπικής -έχει πολύ σημαντικό ρόλο [196]. Στις περισσότερες κοιλιακές επεμβάσεις η λαπαροσκοπική προσέγγιση έχει συνδεθεί με σημαντικά μικρότερο βαθμό μετεγχειρητικών συμφύσεων και επανεισαγωγών που σχετίζονται με αυτές, ενώ έχει βρεθεί ότι οι μεταβολές των μηχανισμών πήξης και ινωδόλυσης που συνοδεύουν τις ανοιχτές επεμβάσεις δεν παρατηρούνται στις λαπαροσκοπικές [63,165].…”
Section: συμφυτικός αποφρακτικός ειλεός (σαε)unclassified
“…PAI και uPA, καθώς και στην δραστηριότητα του tPA σε δείγματα ιστών που λήφθηκαν στην αρχή και στο τέλος των λαπαροσκοπικών επεμβάσεων, όταν αυτές δεν παρατείνονταν ιδιαίτερα. Αντίθετα, η μεγάλη χρονική διάρκεια (μεγαλύτερη των 90 λεπτών) των επεμβάσεων οδηγούσε, όπως ακριβώς και στην περίπτωση των ανοιχτών επεμβάσεων σε μείωση της ινωδολυτικής δραστηριότητας του περιτοναίου[63,165,166].Κατά τις λαπαροσκοπικές επεμβάσεις καίριο ρόλο για τη δημιουργία συμφύσεων φαίνεται να κατέχει το CO2, καθώς έχει βρεθεί ο βαθμός τους σχετίζεται τόσο με τη διάρκεια του πνευμοπεριτοναίου όσο και με το ύψος της ενδοκοιλιακής πίεσης[167,168]. Σε πειραματική μελέτη με τη χρήση πειραματόζωων βρέθηκε ότι το CO2 αυξάνει τις συμφύσεις σε βαθμό που εξαρτάται από το χρόνο και την πίεση και η προσθήκη 2%-4% οξυγόνου μπορεί να εξαλείψει αυτή την επίδραση, γεγονός που υποστηρίζει την υπόθεση ότι ο παθογόνος μηχανισμός σχετίζεται με την υποξία[169].…”
unclassified